O-032 Microcatheter delivery of neurotherapeutics: compatibility with mesenchymal stem cells. (22nd July 2019) - Srinivasan, V; Gumin, J; Camstra, K; Chen, S; Johnson, J; Lang, F; Kan, P
Abstract : Background: Mesenchymal stem cells (MSCs) are being studied for the treatment of several neurological disorders. The use of MSCs as delivery modality for targeted viral therapeutic agents for the treatment of intracranial pathologies has not been explored. Delta-24-RGD, a tumor-selective oncolytic adenovirus designed to target malignant glioma cells, has been shown effective in animal models. However, the most efficient viral tissue delivery modality is unclear. Bone marrow human MSCs (BM-hMSC) have been shown to have homing capability toward glioma xenografts and the feasibility of oncolytic virus particles loaded in MSCs being delivered to the tumor vascular bed via selective intra-arterial (IA) infusion is being investigated. To evaluate the feasibility of endovascular IA delivery, catheter compatibility with MSCs was tested in vitro. Methods: BM-hMSCs were cultured, transfected with Delta-24, and re-suspended in 1% Human Serum Albumin. hMSC-Delta-24 solution was then injected via three microcatheters of different inner diameters (Marathon, Echelon-14, and Marksman). Cell count and viability after injection through the microcatheters based on injection velocity and catheter configuration were assessed. Transwell assay was performed with the injected cells to test the Delta-24 activity against U87 glioma cells. hMSC-Delta-24 compatibility was also tested with commonly used medications in neuroendovascular therapy (Omnipaque, verapamil, and heparin). Results: BM-hMSC cell count prior to infusion was 0.123 × 10 6 cells/mL, 98.7% viability. There was no significant difference in cell count after infused through any of the catheters under standard conditions, with a mean concentration of 0.126 × 10 6 cells/mL and 97.9% (±1.7%) viability. Injection velocity ranged from 1.01 to 73.17 cc/min, with no significant difference in cell count or viability. The same result was seen in either tortuous or straight microcatheter configurations. Cell count and viability did not change significantly when the hMSC in solution was stored for up to 5 hours on ice or mixed with Omnipaque, verapamil, and heparin. Notably, anti-glioma activity was maintained after microcatheter infusion. Conclusions: BM-hMSCs are compatible with a wide variety of commonly used neuroendovascular microcatheters and medications. Stem cell viability and viral agent activity do not appear to be affected by catheter configuration or injection velocity. Commercially available microcatheters can be used to deliver IA stem cell neurotherapeutics. Disclosures: V. Srinivasan: None. J. Gumin: None. K. Camstra: None. S. Chen: None. J. Johnson: None. F. Lang: None. P. Kan: 2; C; Stryker, Medtronic, Cerenovus.